Cam Elyaf Katkılı Betonların Yarmada Çekme Dayanımlarının Yapay Sinir Ağları İle Tahmini - Yıldız, Servet; Bölükbaş, Yakup; Keleştemur, Oğuzhan (My University, 2011)
In this study, split tensile strength of the concrete specimens, which have water-cement ratios of 0.45, 0.50 and 0.55, dosages of 300, 350 and 400, five various ratio of glass fiber, were modeled with artificial neural network (ANN). The data which were provided by ANN model were compared with the data obtained from experimental study and a good agreement was determined between the results.
Bildiri - Yayımlanmış
Keywords: Glass fiber; Concrete